Science fiction film : a critical introduction - Johnston, Keith M. (Berg film genres series, 2011)
"Science Fiction Film develops a historical and cultural approach to the genre that moves beyond close readings of iconography and formal conventions. It explores how this increasingly influential genre has been constructed from disparate elements into a hybrid genre. Going beyond a textual exploration of these films, this study places them within a larger network of influences that includes studio politics and promotional discourses. The book also challenges the perceived limits of the genre - it includes a wide range of films, from canonical SF, such as Le voyage dans la lune, Star Wars and Blade Runner, to films that stretch and reshape the definition of the genre. This expansion of generic focus offers an innovative approach for students and fans of science fiction alike"--